THE TEACHERS"™ EFFICACY IN DESIGNING LESSON PLAN FOR PRIMARY SCHOOL AND THE TEACHERS"™ BACKGROUNDS - Elvisa, Martina; Ikhsanudin, Ikhsanudin; Sada, Clary (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
The purpose of this study is to investigate how well is the teachers"™ efficacy in designing simplified lesson plan for primary school, the relationship between teachers"™ efficacy in designing lesson plan and teachers"™ backgrounds and to find out what background that perform an efficacious result in designing simplified lesson plan for primary school. The participants of this research were teachers of English subject in private schools of Pontianak city, Kalimantan Barat, Indonesia. There were twenty teachers according to the data gathered from Institution of Educational Quality Assurance, LPMP (Lembaga Peningkatan Mutu Pendidikan) Pontianak City for academic year 2020/2021. It consisted of sixteen (16) female teachers and four (4) male teachers. The qualitative data collected in form of teachers"™ lesson plan which were analysed and identified. The result discovered that the teachers have an "average to good" efficacy in designing lesson plan. It was also dicoverd there was relationship between teachers"™ efficacy and teachers"™ background. Those twenty lesson plans identifed that certified teachers performed an excellent efficacy in designing lesson plans. The teachers who graduated from English teacher training program bachelor also showed good efficacy in designing lesson plan. Therefore male teachers performed good efficacy too in designing lesson plan. The result answered the research questions that there was relationship between teachers"™ efficacy in designing lesson plan and teachers"™ backgrounds. The teachers"™ backgrounds such as certified teachers, teachers who graduated from English teacher training program and male teachers, they performed an efficacious result in designing simplified lesson plan.